Robinson Crusoe - Defoe, Daniel, 1661?-1731.; Crowley, J. Donald (Joseph Donald) (Oxford ; New York : Oxford University Press, 1998)
Crusoe leaves the English coast for Africa and finds himself the sole survivor of a shipwreck. On a desert island, he finds another human footprint on the shore, encounters cannibals, and befriends a native.
Originally issued in series: World's classics.
Includes bibliographical references (pages xxvii-xxviii).
Print version record.
eBooks on EBSCOhost
Keywords: Crusoe, Robinson -- (Fictitious character); Crusoe, Robinson (Fictitious character) -- Fiction; Shipwreck survival -- Fiction; Castaways -- Fiction; Solitude -- Fiction; Islands -- Fiction; Survie après naufrages -- Romans, nouvelles, etc; Naufragés -- Romans, nouvelles, etc; Solitude -- Romans, nouvelles, etc; Îles -- Romans, nouvelles, etc; FICTION -- Action & Adventure; Castaways; Islands; Shipwreck survival; Solitude; Fiction; Adventure fiction; Action and adventure fiction